2016
DOI: 10.1002/rcs.1780
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic model for predicting urinary incontinence after robot‐assisted radical prostatectomy

Abstract: We developed a novel prognostic model based on preoperative patient data that can be used for patient counselling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 33 publications
(35 reference statements)
5
21
0
Order By: Relevance
“…CR gradually improves at these times. Our results are in agreement with the recent study by Honda and assists which found that CRs at one, three, and six months were 40.7%, 63.0%, and 73.1%, respectively [15]. The definition of postoperative urinary continence varied among several studies.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…CR gradually improves at these times. Our results are in agreement with the recent study by Honda and assists which found that CRs at one, three, and six months were 40.7%, 63.0%, and 73.1%, respectively [15]. The definition of postoperative urinary continence varied among several studies.…”
Section: Discussionsupporting
confidence: 92%
“…Despite technical and methodological improvements in RP, UI does occur and negatively affects quality of life [17]. Assessment of predictors associated with urinary continence has been tried in many studies [7,15,18,19]. This is important for patients and surgeons [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite technical and methodological improvements in RP, UI does occur and negatively affects quality of life [17]. Assessment of risk factors associated with UI has been tried in many studies [7,14,18,19]. This is important for patients and surgeons [18].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yanagiuchi and co-workers examined and identified outcomes one and three months post RARP, while Olgin and Haga analyzed and evaluated outcomes three and 12 months after surgery [11][12][13]. In addition, Honda and colleagues reported continuous outcomes from one to six months postoperatively [14].…”
Section: Introductionmentioning
confidence: 99%